Strategic discrimination and the emergence of systematic exclusion - Paulo Arvate; Lisa Lenz; Sergio Mittlaender (Empirical Economics, 2023)
This paper studies how individuals consider other individuals' preferences when selecting whom to include in a group or network in the absence of any personal taste or statistical reason associated with the inclusion of a particular applicant. This type of decision emerges, for instance, when unprejudiced white landlords discriminate against black applicants because of the prejudice of existing white tenants, or when employers hire an employee-referred candidate instead of an outsider who is disfavored by current employees. We investigate the potential causes as to why selectors consider the group composition preferences of other group members. First, selectors have altruistic feelings toward them and select their preferred candidates. Second, selectors anticipate that their cooperativeness depends on who will be included and so strategically select candidates who are preferred by current group members. We investigate the reasons for this type of discrimination in an experiment in which we allow for endogenous group formation and show that discriminatory behavior in embedded contexts emerges even when selectors have no taste for any candidate nor any reason to discriminate statistically, but still discriminate in favor of a current group member's preferred candidate both for altruistic and strategic reasons. We thereby identify a new major source for discrimination and for the perpetuation of systematic exclusion of outsiders disfavored by insiders, even when the latter do not participate in the decision of whom to include. We discuss the implications for policies aimed at overcoming strategic discrimination in hiring decisions, employee referral programs, quotas, and bonus payments.
Keywords: C91; J15; 330; Discrimination; Social preferences; Social distance; Exclusion; Public good game